Legal Implications in The Execution of a Will Without Making a Will Authentic Deed in the Conception of Legal Certainty - Nuha, Revana Mahran; Hafidz, Jawade (TABELLIUS: Journal of Law, 2025)
Abstract. The legal system in Indonesia is pluralistic in nature, in which it applies as a legal system that has its own characteristics and structure, namely the customary legal system, the Islamic legal system, the western legal system (civil). In this case, inheritance law is also regulated in it. Where in Islam, a "will" is an act of someone giving an object or benefit to another person or institution/legal entity, which is valid after the giver dies, the research method uses a normative legal approach. The specification of legal research that will be used in this writing is descriptive research, the method of data collection in this study through literature studies and documentation studies. Data analysis in a systematic way includes data reduction, data presentation and drawing conclusions. Based on the research results, it can be concluded that the Legal Implications for the Implementation of a Will Without Making an Authentic Deed in the Concept of Legal Certainty, namely the legal certainty of a will without a Notary deed in the KHI with the Civil Code is that it has a written legal basis, is the last statement of the testator after before he died and its implementation after the testator dies, can be revoked and can be cancelled or canceled, has the aim of human welfare so that there is no dispute between the heirs. The difference between a will without a Notary deed in the KHI is a minimum age of 21 years while the Civil Code is a minimum age of 18 years, seen from the recipient of the will in the KHI, namely another person or institution while the Civil Code is an outsider and the heir, seen from its form in the KHI, namely oral or written or before a Notary while the Civil Code is written before a Notary or deposited/stored by a Notary. Legal Protection for Will Recipients Who Make Wills Without Making an Authentic Deed If There is a Dispute Between the Parties, namely the legal consequences of wills without a Notarial deed, making the will vulnerable to lawsuits from interested parties because the evidence is not strong enough and there is no legal certainty. According to the KHI and the Civil Code, wills need to be proven authentically, this is intended so that negative things that are not desired by the testator or the will recipient do not occur.Keywords: Certainty; customary; Legal; Notarial.